2020
DOI: 10.3389/fnhum.2020.00361
|View full text |Cite
|
Sign up to set email alerts
|

Altered Static and Dynamic Spontaneous Neural Activity in Drug-Naïve and Drug-Receiving Benign Childhood Epilepsy With Centrotemporal Spikes

Abstract: The present study aims to investigate intrinsic abnormalities of brain and the effect of antiepileptic treatment on brain activity in Benign childhood epilepsy with centrotemporal spikes (BECTS). Twenty-six drug-naïve patients (DNP) and 22 drug-receiving patients (DRP) with BECTS were collected in this study. Static amplitude of low frequency fluctuation (sALFF) and dynamic ALFF (dALFF) were applied to resting-state fMRI data. Functional connectivity (FC) analysis was further performed for affected regions ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…This further supports the theory that neuromagnetic signals of different frequency bands represent distinct inherent physiological activities (Tenney et al, 2014;Tang et al, 2016;Zhang et al, 2020). In agreement with fMRI evidence based on amplitude of low frequency fluctuation (Jiang et al, 2020) and functional covariance connectivity (Jiang et al, 2019), our results suggest that AEDs have effects on brain regional activity and functional networks. The analysis of the magnetic source location exhibited that, after treatment, activation of PCC increased in multiple frequency bands, and the differences were evident in the 30-80 Hz frequency band.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This further supports the theory that neuromagnetic signals of different frequency bands represent distinct inherent physiological activities (Tenney et al, 2014;Tang et al, 2016;Zhang et al, 2020). In agreement with fMRI evidence based on amplitude of low frequency fluctuation (Jiang et al, 2020) and functional covariance connectivity (Jiang et al, 2019), our results suggest that AEDs have effects on brain regional activity and functional networks. The analysis of the magnetic source location exhibited that, after treatment, activation of PCC increased in multiple frequency bands, and the differences were evident in the 30-80 Hz frequency band.…”
Section: Discussionsupporting
confidence: 90%
“…First, the number of participants who completed the follow-up was less than expected, and the small sample size weakened the statistical power and the generalizability of the conclusions, to some extent. Meanwhile, this study design was not able to compare brain activity between untreated CECTS children and matched healthy controls, so while several previous studies have reported comparative results for this purpose among untreated children and healthy controls (Jiang et al, 2019(Jiang et al, , 2020Li et al, 2020b), we still cannot assert that all the cognitive improvements can be attributed to AEDs. Additionally, this study, limited by sample size, did not group the types of AEDs and the prognosis of the children, which can cause mixed effects.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Functional images were preprocessed using a software (Data Processing and Analysis for Brain Imaging toolbox; http://rfmri.org/DPABI ) ( 46 ). The main steps were included: (1) exclusion of the initial 10 volumes to ensure signal stability; (2) slice timing and realignment; (3) spatial normalization to the standard Montreal Neurological Institute (MNI 152) space and resampled to 3 × 3 × 3 mm 3 ; (4) spatial smoothing using a 6-mm full-width half-maximum Gaussian kernel; (5) detrending the BOLD signals to correct a linear trend; (6) regression out of the nuisance covariates including the averaged signals from global mean signals ( 22 , 28 , 30 , 47 ), cerebrospinal fluid signals, white matter signals, and Friston-24 head motion parameters; (7) temporal filtering (bandpass, 0.01–0.08 Hz) of BOLD signals; (8) to exclude the influence of head motion and ensure the contiguous time points, scrubbing with cubic spline interpolation was used; (9) additionally, to evaluate the head movement, we also calculate the mean frame-wise displacement (FD) ( 48 , 49 ). In the group-level analysis, we also used the mean FD as a covariate to reduce the impact of motion artifact in the fMRI signal.…”
Section: Methodsmentioning
confidence: 99%
“…In a literature search of the aforementioned IBA dynamic indicators, most research on TLE was found to focus on dynamic FC studies ( Jiang et al, 2020 ; Li et al, 2022 ; Pang et al, 2022 ). However, the relevant studies which applied the other dynamic indicators, such as dALFF, dfALFF, dReHo, dDC, dVMHC and dGSCorr, in TLE patients could not be retrieved.…”
Section: Introductionmentioning
confidence: 99%